2006
DOI: 10.1016/j.jpainsymman.2006.05.018
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Videoconferencing to Provide Innovative Delivery of Psychological Treatment for Rural Cancer Patients: Results of a Pilot Study

Abstract: The unmet psychological needs of rural cancer patients are numerous. Telepsychology is a novel and feasible option that may provide cost-savings and help overcome inequalities in access to specialists. This is the first known study of psychological treatment for people with cancer delivered entirely via videoconferencing. We hypothesized that a telepsychology service would improve rural cancer patients' anxiety and depression levels and quality of life, and would be an acceptable, satisfactory, and practical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 33 publications
1
73
0
7
Order By: Relevance
“…64 In Rehabilitation, Disability and Ageing a single group design, 25 cancer patients with varying diagnoses and stages of disease received an average of 3 sessions with a clinical psychologist providing brief CBT. The results indicated that patients experienced significant changes, with reduced anxiety and improved quality of life.…”
Section: Remote Counselling Via Videoconferencingmentioning
confidence: 99%
“…64 In Rehabilitation, Disability and Ageing a single group design, 25 cancer patients with varying diagnoses and stages of disease received an average of 3 sessions with a clinical psychologist providing brief CBT. The results indicated that patients experienced significant changes, with reduced anxiety and improved quality of life.…”
Section: Remote Counselling Via Videoconferencingmentioning
confidence: 99%
“…Por ejemplo en una videoconferencia hay que adaptar el ritmo y la velocidad de las verbalizaciones ya que por pequeños retrasos en la transmisión se debe tener especial cuidado en esperar la respuesta y la finalización del interlocutor para plantear algún nuevo mensaje, evitando la frustración que provoca el sobreponer conversaciones (Rees y Stone, 2005;Shepherd, et al, 2006). Por otro lado se debe prestar especial atención a cómo desarrollar textos y gráficos que favorezcan la comprensión, la empatía y promuevan el cambio.…”
Section: Preparándose Para Desarrollar Una Ciber-terapia: Algunos Aspunclassified
“…y ¿dónde puedo ir? (Chiu y Shepherd, et al, 2006;World Wide Web Consortum, 1999). En este punto de diseño tecnológico y usabilidad, es fundamental señalar que los estudios sobre ciber-terapias habitualmente incluyen participantes info-alfabetizados (Andersson, 2009); contrariamente, para lograr una real diseminación de estos tratamientos se debe tener especial cuidado y dedicación en los elementos de accesibilidad web los que deben permitir una utilización universal que realmente fomente y facilite el acceso a la salud universal y, especialmente, para los más desfavorecidos que, habitualmente, no son usuarios informáticos.…”
Section: Preparándose Para Desarrollar Una Ciber-terapia: Algunos Aspunclassified
See 1 more Smart Citation
“…El uso de Internet, por ejemplo, ha posibilitado que los programas terapéuticos puedan llegar a aquellos pacientes que les resulta difícil el traslado hasta sus centros de salud, ya sea por la enfermedad, la ubicación geográfica o cualquier otra razón (1)(2)(3) . Otro ejemplo lo constituyen los denominados "juegos serios" (serious games), juegos digitales creados con propósitos que van más allá del entretenimiento, que facilitan la entrega de información médica y de herramientas de apoyo para la toma decisiones y la implicación en conductas saludables (4)(5)(6) .…”
Section: Introductionunclassified